Attitude of Drugstore Entrepreneurs Towards on the Development Drugstores to GPP Standard - Manivong, Phoutsalin; HOONGSENGPHA, Soudtida; INDAVONG, Dalounny (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The objectives of this research were to study the components of attitude, including the Cognitive, opinions, and behavioral trends towards the development of quality pharmacies that meet GPP standards, this was a study in accordance with the pharmacy standard requirements of the Ministry of Public Health, To be used to create a tool to collect information from 60 drugstore Entrepreneurs in Luang Prabang city, by using SPSS statistical software to help calculate. Analyze data and explain the results according to the objectives of the study. The results of the study found that Most drugstore businesses in Luang Prabang are drugstores that were established as private enterprises and use their own funds in the first-class pharmacy category, The business has been in business for between 7-9 years, provide technical services yourself, it was open for business as usual from morning to evening and was a store located in the municipality. The pharmacy Entrepreneurs in Luang Prabang city had a high cognitive about the pharmacy standard. In this regard, the pharmacy Entrepreneurs have a mediocre level of knowledge and understanding about the pharmacy data storage system; As for opinions on quality pharmaceutical standards (GPP), overall, there was a high level of agreement in all aspects. For the behavioral trend of pharmacy Entrepreneurs in Prabang city towards the development of quality pharmacy (GPP) with most of them didn’t wanting to develop their own pharmacy to become a quality pharmacy (GPP). The reason being: There was still no readiness for expenses in improving and developing the store, which will cause the cost of selling drugs to increase. And currently, customers in Luang Prabang still don’t give importance to this aspect as they should. The results of the logistic regression analysis as follows in the standard of development as a quality pharmacy (GPP) all include 5 aspects, there is only one aspect by service provision and participation with community and society that have a relationship and effect on the development requirements as a quality pharmacy (GPP) at a 95% reliability level.